EVALUATION OF HYBRIDIZATION BETWEEN PANGASIUS DJAMBAL BLEEKER 1846 AND PANGASIANODON HYPOPHTHALMUS (SAUVAGE 1878): BIOMETRIC CHARACTERIZATION AND GROWTH ANALYSIS - Rudhy Gustiano; Anang Hari Kristanto (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2007)
Possible use of pangasiid hybrids in aquaculture might generate potential impacts on wild populations. Therefore, rapid identification tools in the field such as growth rate are urgently needed. This study examines morphological characters and growth performance of P. djambal and P. hypophthalmus and their reciprocal hybrids. A detailed morphological study analysed 32 morphometric measurements and 5 meristic counts on hybrids of Pangasius djambal and P. hypophthalmus. Morphometric analysis and meristic counts showed that the reciprocal hybrids have intermediate characters except for gill rakers number which were lower than that of parental species. In general, the hybrids have tendency to be like P. hypophthalmus rather than P. djambal. The only typical character P. djambal appearing in hybrids is teeth shape, both vomerine and palatine. It was shown that the true hybrids have seven pelvic fin rays. Eight months of growth comparison in earthen ponds showed that the hybrids have a better performance for specific growth rate than the parental stock.